Effikasi Diri dan Performansi Akademik: Studi Meta Analisis - Lie Fun Fun (Universitas Kristen Maranatha, 2021)
This meta-analysis study aims to see how the true correlation between self-efficacy and academic performance. Publications in the literature are gathered by investigating articles related to the theme. Based on the criteria set by researcher from 15 journals which are the results of research from the period 2006 to 2020, 16 studies were found in the analysis. Journal searches are obtained through an online data base. Data analysis was performed using 2 meta-analysis techniques for artifact data, namely correction of sampling errors and correction of measurement errors. The meta-analysis was carried out with a total sample size of N = 5039. The results of the meta-analysis show that self-efficacy has a positive correlation with academic performance of 0,399. Keywords: meta-analysis, self-efficacy, academic performance